Rooted jazz dance : Africanist aesthetics and equity in the twenty-first century - Guarino, Lindsay; Jones, Carlos R. A.; Oliver, Wendy (University Press of Florida, 2022)
"Decolonizing contemporary jazz dance practice, this book examines the state of jazz dance theory, pedagogy, and choreography in the twenty-first century, recovering and affirming the lifeblood of jazz in Africanist aesthetics and Black American culture"--